Dietary butylated hydroxytoluene improves lipid metabolism, antioxidant and anti-apoptotic response of largemouth bass (Micropterus salmoides). Issue 72 (January 2018) - Yu, L.L.; Yu, H.H.; Liang, X.F.; Li, N.; Wang, X.; Li, F.H.; Wu, X.F.; Zheng, Y.H.; Xue, M.; Liang, X.F.
Abstract: A 10-week growth trail was conducted to investigate the efficacy and tolerance of dietary butylated hydroxytoluene (BHT) by evaluating inflammation, apoptosis and hepatic disease related to oxidative stress in largemouth bass ( Micropterus salmoides ). Four experimental diets were prepared with BHT supplement levels of 0 (B0), 150 (B150), 300 (B300) and 1500 (B1500) mg/kg, in which B150 was at the maximum recommended level established by European Union Regulation, and the B300 and B1500 levels were 2 and 10-fold of B150, respectively. Each diet was fed to 6 replicates with 30 largemouth bass (initial body weight, IBW = 6.20 ± 0.01 g) in each tank. The BHT inclusion level did not affect the specific growth rate, but fish in the B150 group showed the lowest feed conversion rate ( P < 0.05). BHT inclusion significantly decreased the levels of plasma TC, TG, LDL, ALT and AKP, and increased the (HDL-C)/TC ratio ( P < 0.05). Plasma MDA was significantly decreased in the B150 group and GSH-Px was extremely enhanced in each BHT inclusion group ( P < 0.05). Hepatic T-AOC was significantly enhanced and O2 − was significantly decreased in each BHT inclusion group compared to the B0 group ( P < 0.05), as well as hepatic MDA was significantly decreased in B1500 group ( P < 0.05). Dietary BHT inclusion down-regulated the hepatic mRNA levels of inflammation, apoptosis and fibrosis related genes, including TNFα, TGF-β1, α-SMA, IL8, IL11β and caspase-9. Moreover, BHT could improve hepatic lipid metabolism via up-regulating the mRNA levels of APOA1, CYP7A1, CYP8B1, and down-regulating the mRNA levels of PPAR-γ and APOB. Histological examination of the liver morphology with H&E and Sirius Red staining showed that BHT inclusion decreased necrotic degenerative changes and collagen deposition in largemouth bass. An immunofluorescence examination revealed significantly decreased cleaved caspase-3 signals in the BHT groups. In conclusion, the results demonstrated that ROS induces hepatic cell apoptosis and fibrosis via the intrinsic pathway of apoptosis by activating caspase-9 in the mitochondria and then initiates apoptosis by activating caspase-3. Consuming 2.32–23.80 mg/kg·bw/d (150–1500 mg/kg in diet) of BHT effectively improved the plasma and hepatic lipid metabolism, antioxidant response as well as reduced ROS production, protecting hepatic cells from injury. It is implied that even a 10-fold increase of the maximum level of BHT (150 mg/kg) is safe for the largemouth bass. Highlights: Consuming 2.32–23.80 mg/kgbw/d of BHT improved hepatic function and lipid metabolism of largemouth bass. The antioxidant response, especially plasma glutathione peroxidase was enhanced by BHT inclusion. Plasma and hepatic ROS production were significantly reduced by BHT inclusion. ROS induces apoptosis/fibrosis by activating caspase-9 in mitochondria and then activates apoptosis by cleaving caspase-3. Ten-fold of the maximum level of BHT (150 mg/kg) designated by EU regulations is safe for largemouth bass.